2019
DOI: 10.1590/1807-1929/agriambi.v23n4p237-243
|View full text |Cite
|
Sign up to set email alerts
|

Phytosanitary quality of Brachiaria brizantha ‘BRS Piatã’ seeds in function of climate conditions

Abstract: Infected seeds are one of the main pathogen transmission vehicles, and they are responsible for significant losses in production fields; phytosanitary defense depends on the inoculum and climatic factors. Thus, in this study, it was aimed to identify climatic variables of the regions that propitiate the production of Brachiaria brizantha 'BRS Piatã' seeds infected with phytopathogenic fungi. Temperature and rainfall data were obtained from 10 production fields, and phytosanitary quality of the seeds was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This technique has been used in seed technology research with the aim of clarifying the relationships between the different variables evaluating physiological potential. Moreover, it has been successfully used for soybean seeds (Barbosa et al, 2013), forage grasses of the Brachiaria genus (Silva et al, 2017;Silva et al, 2019), and caupi beans (Mendonça et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been used in seed technology research with the aim of clarifying the relationships between the different variables evaluating physiological potential. Moreover, it has been successfully used for soybean seeds (Barbosa et al, 2013), forage grasses of the Brachiaria genus (Silva et al, 2017;Silva et al, 2019), and caupi beans (Mendonça et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These values are similar to those found in studies on the physiological and sanitary quality of Urochloa brizantha cv. BRS Piatã [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate data analysis methods allow a global study of these variables, evidencing the connections, similarities, or differences between them with the least possible loss of information [ 26 , 29 , 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies confirmed the identification of C. maximensis and Brachiaria grasses in Brazil (Chaves, Gomes, Marriel, & Pfenning, 2004), and recent studies show that 50% commercial seed lots of B. brizantha cv. Piatã collected in 10 seed production fields (two seed production fields in each state of Brazil: SP, GO, BA, MG and MS) were infected with more than one species of Claviceps (Silva, Martins, Nascimento, Barreto, & Farias, 2019). The association of pathogens to seeds can affect plant establishment, development, seed production, forage persistence in the field and animal production.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fungicides in the soil may reduce the presence of the pathogen (Fernandes, Verzignassi, Mallmann, & Queiroz, 2017;Dung et al, 2018), but the selection of resistant forage grasses would be the most effective management (Miedaner & Geiger, 2015). Considering that Brazil is the leading producer and exporter of tropical seeds of forage grasses in the world (Silva et al, 2019), the commercialization of contaminated seed lots can affect mainly the foreign market, due to restrictions on the presence of Claviceps spp. in many countries.…”
Section: Introductionmentioning
confidence: 99%